High-Growth Entrepreneurship - J. David Brown; John S. Earle; Mee Jung Kim; Kyung Min Lee (Institute of Labor Economics (IZA), 2018)
Analyzing data on all U.S. employers in a cohort of entering firms, we document a highly skewed size distribution, such that the largest 5% account for over half of cohort employment at firm birth and more than two-thirds at firm age 7. Little of the size variation is accounted for by industry or amount of finance, but relative size is strongly persistent over time: at age 7, the probability of 20+ employees is about 40 times larger for those entering with 20+ than for those entering with one. We link administrative and survey data to study the role of founder characteristics in high growth, defined as the largest 5% of the cohort at ages 0 and 7. Female-founded firms are 50% less likely to be in this ventile at both ages, and 34% less likely when controlling for detailed demographic and human capital variables. A similar initial gap for African-Americans, however, disappears by age 7. Founder age is positively associated with high growth at entry, but the profile flattens and turns negative as the firm ages. The education profile is initially concave, with graduate degree recipients no more likely than high school graduates to found high growth firms, but the former nearly catch up to those with bachelor's degrees by firm age 7, while the latter do not. Most other relationships of high growth with founder characteristics are highly persistent over time. Prior business ownership is strongly positively associated, and veteran experience negatively associated, with high growth. A larger founding team raises the probability of high growth, while, controlling for team size, diversity (by gender, age, race/ethnicity, or nativity) either lowers the probability or has little effect. Controlling for start-up capital raises the high-growth probability of firms founded by women, minorities, immigrants, veterans, smaller founding teams, and novice, younger, and less educated entrepreneurs. Perhaps surprisingly, female, minority, and less-educated entrepreneurs tend to choose high-growth industries, but fewer of them achieve high growth relative to their industry peers.
Keywords: D22; J24; L25; L26; 330; entrepreneurship; business entry; firm growth; firm dynamics; founder; employment; firm size distribution; firm performance